(untitled) (Damascus University Journal of agriculture sciences, 2024)
A study was conducted at the Deir Al-Hager camel’s research center, Animal Wealth Administration, Damaascus in 2019-2020. In order to determine the concentrations of IgG, IgM, sodium, and iron in camel milk, thirty lactating Shami camels were chosen in their first to sixth parity. The mean values reported were 2.62± 0.79 mg/ml , 1.53±0.45 mg/ml, 650.78 ±121.59 mg/l and 2.68 ±1.36 mg /l for IgG, IgM, sodium and iron, respectively. Parity and month of location affected significantly P< 0.05 on the Concentrations of both IgG and sodium that their levels increased gradually by the subsequent parity, but during the course of lactation while the concentration of sodium increased, the concentration of IgG decreased. The month of lactation affected (P< 0.05) IgM and iron content in the milk, with the highest values of IgM in the first month, but for iron its highest values were in the sixth month of lactation.